Analisis Distribusi Temperatur Koefesien Perpindahan Panas pada Sistem Pendingin (Simulasi) Menggunakan Porous Media dengan Variasi Porositas (Sekolah Pascasarjana, Universitas Brawijaya, 2018)
The internal combustion engine is a fairly kece slot old machine and currently has many alternative energy which apparently has not been able to shift the role of the internal combustion engine, for the cooling system in the internal combustion engine greatly affect the performance and if not handled kece slot properly will cause something fatal, ie when the engine is too hot it can cause over heating and the machine can not work anymore. For Cooling system has been using fin and radiator. Research continues to grow in terms of heat transfer, ie by using porous media. Presence of porous media cooling system is expected to replace the role of fin and radiator easier maintenance and able to transfer heat well. In this case the research is assisted by simulation to see the temperature distribution that occurs in porous media with variation of 10%, 15%, 20% 25%, 30% The result of research by using simulation shows that the porosity value of porous media, the temperature distribution value also greater than. then the higher the porosity value the value (h) the heat transfer coefficient will be low. Keywords:Â Heat Transport, Porosity, Temperature